Station-side optical network terminal apparatus, subscriber-side optical network terminal apparatus, and optical communication system - Nakaishi, Hiroshi; Kubota, Tatsuya (2011)
While continuously providing a service in an existing optical communication system, a service at another communication speed is realized at low cost. For this reason, a station-side optical network terminal apparatus is configured so that to one light-emitting unit connected are a first processing unit that performs a process to output an optical signal at one communication speed by the light-emitting unit and a second processing unit that performs a process to output an optical signal at another communication speed by the light-emitting unit.